Pineal gland volumes are changed in patients with obsessive-compulsive personality disorder - Atmaca, Murad; Korucu, Tuba; Kilic, M. Caglar; Kazgan, Asli; Yildirim, Hanefi (Elsevier Sci Ltd, 2019)
Objective: In the present study, taking into consideration our previous studies showing an association on the neuroanatomy of OCD and obsessive-compulsive personality disorders (OCPD), we also decided to examine pineal gland volumes in patients with obsessive-compulsive personality disorder and hypothesized that gland volumes would be found as altered in comparison with those of healthy subjects. Methods: Sixteen patients with OCPD and eighteen healthy control subjects underwent magnetic resonance imaging (MRI). We compared the volumes of pineal gland by using MRI between groups. Results: As compared to healthy control subjects, patients with OCPD had statistically significant smaller pineal gland volumes by using independent sample t test (87.34 +/- 19.72 mm(3) for patients with OCPD vs. 108.62 +/- 22.56 mm(3), with a statistically significantly difference of p < 0.01.When controlling for gender distribution, age and whole brain volumes in the General Linear Model, we saw that patients with OCPD had still statistically significant smaller pineal volumes compared to those of healthy control subjects. Conclusion: Finally, the findings of the present study revealed that patients with OCPD had reduced pineal gland volumes compared to those of healthy control subjects, supporting the fact that OCPD might be included in the OCD spectrum disorders, since we have previously found same result in patients with OCPD. (C) 2019 Published by Elsevier Ltd.
Keywords: OCPD; Personality disorder; Pineal gland; Volumes; MRI